Research gaps in the philosophy of evidence‐based medicine. Issue 11 (November 2016) - Mebius, Alexander; Kennedy, Ashley Graham; Howick, Jeremy
Abstract: Increasing philosophical attention is being directed to the rapidly growing discipline of evidence‐based medicine (EBM). Philosophical discussions of EBM, however, remain narrowly focused on randomization, mechanisms, and the sociology of EBM. Other aspects of EBM have been all but ignored, including (a) the nature of clinical reasoning and the question of whether it can be standardized; (b) the application of EBM principles to the logic, value, and ethics of diagnosis and prognosis; (c) evidence synthesis (systematic reviews and meta‐analyses); and (d) the nature and ethics of placebo controls. Philosophical analysis in each of these areas has the potential to enhance the discussion of EBM methodology and practice.